Novel ICD Programming and Inappropriate ICD Therapy in CRT-D Versus ICD Patients: A MADIT-RIT Sub-Study. (January 2016) - Kutyifa, Valentina; Daubert, James P.; Schuger, Claudio; Goldenberg, Ilan; Klein, Helmut; Aktas, Mehmet K.; McNitt, Scott; Stockburger, Martin; Merkely, Bela; Zareba, Wojciech; Moss, Arthur J.
Abstract : Background—: The Multicenter Automatic Defibrillator Implantation Trial–Reduce Inappropriate therapy (MADIT-RIT) trial showed a significant reduction in inappropriate implantable cardioverter defibrillator (ICD) therapy in patients programmed to high-rate cut-off (Arm B) or delayed ventricular tachycardia therapy (Arm C), compared with conventional programming (Arm A). There is limited data on the effect of cardiac resynchronization therapy with a cardioverter defibrillator (CRT-D) on the effect of ICD programming. We aimed to elucidate the effect of CRT-D on ICD programming to reduce inappropriate ICD therapy in patients implanted with CRT-D or an ICD, enrolled in MADIT-RIT. Methods and Results—: The primary end point of this study was the first inappropriate ICD therapy. Secondary end points were inappropriate anti-tachycardia pacing and inappropriate ICD shock. The study enrolled 742 (49%) patients with an ICD and 757 (51%) patients with a CRT-D. Patients implanted with a CRT-D had 62% lower risk of inappropriate ICD therapy than those with an ICD only (hazard ratio [HR] =0.38, 95% confidence interval: 0.25–0.57; P <0.001). High-rate cut-off or delayed ventricular tachycardia therapy programming significantly reduced the risk of inappropriate ICD therapy compared with conventional ICD programming in ICD (HR=0.14 [B versus A]; HR=0.21 [C versus A]) and CRT-D patients (HR=0.15 [B versus A]; HR=0.23 [C versus A]; P <0.001 for all). There was a significant reduction in inappropriate anti-tachycardia pacings in both group and a significant reduction in inappropriate ICD shock in CRT-D patients. Conclusions—: Patients implanted with a CRT-D have lower risk of inappropriate ICD therapy than those with an ICD. Innovative ICD programming significantly reduces the risk of inappropriate ICD therapy in both ICD and CRT-D patients. Clinical Trial Registration—: http://clinicaltrials.gov ; Unique identifier: NCT00947310.